WFH WLB And Their Effects On Employees’ Performance During The Pandemic Era: A Conceptual Framework - Muhammad Fahrizal Hasibuan; Sopiah Sopiah (Indonesian Journal of Multidisciplinary Science, 2021)
The COVID-19 pandemic has hit almost all countries, including Indonesia. COVID-19 has had a huge impact on the entire community, especially employees. One of the impacts that occurred was the implementation of Work from Home (WFH), this was done as an effort to reduce the transmission rate of COVID-19. However, the direct effect that occurred was that employees faced several conflicts such as stress, frustration and imbalances in life. On this basis, researchers want to know the role given by work life balance on employee performance during the COVID-19 pandemic. The method used in this research is a study of the literature which is based on studies of previous studies that match the criteria for the same research variables. The results obtained in this study are work life balance by applying flexible time, increasing job satisfaction, and also to increase employee self-control which is predicted to improve the performance of employees who apply WFH.